A billion shots : a travelogue - Lim, Billion; Fong, Sai (Petaling Jaya, Selangor : World Express Mapping)
Consist 8 countries 36 destinations at Southeast Asian
Keywords: Travelers -- Asia, Southeast; Asia, Southeast -- Description and travel